Modeling the biomechanics of the conventional aqueous outflow pathway microstructure in the human eye. (June 2022) - Karimi, Alireza; Razaghi, Reza; Rahmati, Seyed Mohammadali; Downs, J. Crawford; Acott, Ted S.; Wang, Ruikang K.; Johnstone, Murray
Highlights: A 3D microstructural FE model of a human conventional aqueous outflow pathway is constructed. Three different elastic moduli were assigned to the TM/JCT complex. The hydraulic conductivity was programmed separately for the TM, JCT, and SC inner wall. Elevated TM/JCT stiffness caused larger stresses, but smaller strains in the outflow tissues. Elevated TM/JCT stiffness caused larger pressure drop across the SC inner wall. Abstract: Background and objective: Intraocular pressure (IOP) is determined by aqueous humor outflow resistance, which is a function of the combined resistance of Schlemm's canal (SC) endothelium and the trabecular meshwork (TM) and their interactions in the juxtacanalicular connective tissue (JCT) region. Aqueous outflow in the conventional outflow pathway results in pressure gradient across the TM, JCT, and SC inner wall, and induces mechanical stresses and strains that influence the geometry and homeostasis of the outflow system. The outflow resistance is affected by alteration in tissues' geometry, so there is potential for active, two-way, fluid-structure interaction (FSI) coupling between the aqueous humor (fluid) and the TM, JCT, and SC inner wall (structure). However, our understanding of the biomechanical interactions of the aqueous humor with the outflow connective tissues and its contribution to the outflow resistance regulation is incomplete. Methods: In this study, a microstructural finite element (FE) model of a human eye TM, JCT, and SC inner wall was constructed from a segmented, high-resolution histologic 3D reconstruction of the human outflow system. Three different elastic moduli (0.004, 0.128, and 51.5 MPa based on prior reports) were assigned to the TM/JCT complex while the elastic modulus of the SC inner wall was kept constant at 0.00748 MPa. The hydraulic conductivity was programmed separately for the TM, JCT, and SC inner wall using a custom subroutine. Cable elements were embedded into the TM and JCT extracellular matrix to represent the directional stiffness imparted by anisotropic collagen fibril orientation. The resultant stresses and strains in the outflow system were calculated using fluid-structure interaction method. Results: The higher TM/JCT stiffness resulted in larger stresses, but smaller strains in the outflow connective tissues, and resulted in a 4- and 5-fold larger pressure drop across the SC inner wall, respectively, compared to the most compliant model. Funneling through µm-sized SC endothelial pores was evident in the models at lower tissue stiffness, but aqueous flow was more turbulent in models with higher TM/JCT stiffness. Conclusions: The mechanical properties of the outflow tissues play a crucial role in the hydrodynamics of the aqueous humor in the conventional outflow system.